VISTA HORIZON PENALARAN ARKOUN TERHADAP BAHASA KESIMBOLAN AYAT AL-QURAN - Abd Aziz; Ahmad Masruri; Salahuddin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This study discusses Arkoun's reasoning in the interpretation of the Koran. This paper concludes that the language of the Qur'an contains symbols that can contribute to linguistics, which in turn produces linguistic theories and can be related to the context of mythical thinking caused by the symbols that appear in it. Classical interpretation has a tendency to reduce symbolic languages. Arkoun's reasoning is taken from the tradition of Western thought which is outlined in terms that are sometimes difficult to understand, and on the other hand his ideas are able to give their own color to the treasures of Islamic scholarship